DIRECTING FROM A DISTANCE: THE TRANSFORMATIVE ROLE OF TEACHERS AS REMOTE THEATRE DIRECTORS IN ONLINE EDUCATION - Umar; Pujiastuti, Eka (Universitas PGRI Palembang, 2025)
The article explores the metaphor of teachers as remote theatre directors in online education, examining how this analogy illuminates the complex roles of educators in virtual classrooms. It highlights how teachers, like directors, creatively orchestrate lessons and manage student engagement through innovative strategies. By analysing this metaphor, the article sheds light on the adaptive methods educators use to navigate online teaching challenges and enhance the overall learning experience in digital environments. The research utilized qualitative methods, including semi-structured interviews, focus groups, and observations, to explore the metaphor of teachers as remote theatre directors. Key findings revealed that educators creatively adapt traditional methods using multimedia tools and interactive strategies to engage students in virtual settings. The study highlighted challenges such as maintaining connection and addressing technological disparities. The implications suggest that adopting innovative teaching strategies and improving technological support can significantly enhance online education effectiveness and student outcomes.